KARAKTER PRODUK HUKUM DALAM PEMBENTUKAN UU NO 16 TAHUN 2019 - Fatimatuz Zahro; Dzurrotul Muniroh Ahdaniah (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2025)
The formation of legal products in Indonesia, particularly in the field of family law, is inseparable from the dynamics of legal politics, which are marked by ideological, social, and cultural contestations. Law No. 16 of 2019 concerning the Amendment to Law No. 1 of 1974 on Marriage serves as a concrete example of how legal politics shape regulations through compromise. The amendment raising the minimum marriage age for women from 16 to 19 years reflects a responsive legal character, as it was influenced by the Constitutional Court’s ruling and strong advocacy from civil society groups emphasizing child protection and gender equality. This demonstrates the characteristics of responsive law, as theorized by Nonet and Selznick, which underscores the law’s openness to societal aspirations. However, the provision under Article 7 paragraph (2), which still allows for marriage dispensation through the courts, reveals a conservative tendency within the legislation. This provision creates a normative contradiction: on the one hand, the state seeks to prevent child marriage; on the other hand, it legitimizes such practices under certain urgent circumstances. This phenomenon illustrates that family law in Indonesia is not neutral but rather a result of complex political negotiations involving the state, judiciary, religious organizations, and civil society actors. Consequently, Indonesian family law exhibits a dualistic character—responsive in its legislative process, yet conservative in the substance of its provisions. This study highlights the importance of understanding legal politics in evaluating whether family law reforms can genuinely promote substantive justice, human rights protection, and gender equality within society